2017
DOI: 10.1002/bip.22882
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the aggregation propensity of human insulin C‐peptide

Abstract: Over the last 20 years, proinsulin C-peptide emerged as an important player in various biological events. Much time and effort has been spent in exploring all functional features of C-peptide and recording its implications in Diabetes mellitus. Only a few studies, though, have addressed C-peptide oligomerization and link this procedure with Diabetes. The aim of our work was to examine the aggregation propensity of C-peptide, utilizing Transmission Electron Microscopy, Congo Red staining, ATR-FTIR, and X-ray fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that C-peptide has been reported to produce amyloid-like fibrils [36] .⁠ However, the timescale required experimentally for this peptide to develop a fully ordered structure ranges from minutes to days [36] , [47] .⁠ Our results are not contradictory with this biophysical evidence, as our simulations can capture only the early phases of aggregation. Indeed, this goes in line with the long-term effect of maturation and optimization of inter-glutamine interactions observed here.…”
Section: Discussionmentioning
confidence: 54%
“…It is worth mentioning that C-peptide has been reported to produce amyloid-like fibrils [36] .⁠ However, the timescale required experimentally for this peptide to develop a fully ordered structure ranges from minutes to days [36] , [47] .⁠ Our results are not contradictory with this biophysical evidence, as our simulations can capture only the early phases of aggregation. Indeed, this goes in line with the long-term effect of maturation and optimization of inter-glutamine interactions observed here.…”
Section: Discussionmentioning
confidence: 54%
“…NMR studies showed that low pH shifted the conformational landscape of C-peptide towards a higher β-strand content. Electron microscopy, X-ray diffraction and FT-IR eventually confirmed that C-peptide, despite being highly soluble at physiological pH, spontaneously can form amyloid-like fibrils under acidic conditions [41,42].…”
Section: Phase 3: Combined Knowledge Of Structure Function and Evolumentioning
confidence: 87%
“…The conventional 86-AA proinsulin is prefolded into its correct conformation in the Golgi apparatus, together with C-peptide ( 26 ). The N-terminus of the 31-AA C-peptide (EAEDLQVGQ) acts as a chaperone ( 27 ) to promote correct insulin folding, while its C-terminus (EGSLQ), in circulation, is known to bind the orphan G-protein–coupled receptor GPR146 ( 28 ).…”
Section: Discussionmentioning
confidence: 99%